Identifying Medicinal Plant in Local Custom Nasinoah Forest to Develop Local Wisdom Based Learning Material (Universitas Negeri Semarang, 2019)
Biloto villagers who are living nearby Nasinoah forest have strong interaction with the environment. The interaction brings about skills in managing the natural resource to be useful for life particularly making use of any plants as traditional medicine done by mnanet (traditional medical experts). This study aimed at: 1) Identifying and documenting the species of medicinal plants in Nasinoah forest; 2). Creating material and other teaching and learning instruments of biological variety and the use of natural resource based on identification and documentation result; 3) Testing validity and legibility of the material and instruments. The data gathered were the species of medicinal plants and local skills in managing the plants. Interview, survey, and literature were the instruments used to gather data. The study revealed that there were 33 kinds of plant identified as medicinal plants classified into 25 different familys which were used by Biloto villagers. Then, learning material about medicinal plants was arranged as contextual material based on the data. The study concluded that there were variety of medicinal plants used by Biloto villagers as medicine and the contextual teaching and learning instruments were valid and applicable.